Sizing guidelines for grid-connected decentralised energy storage systems: single house application - Panagiotou, Konstantina; Klumpner, Christian; Sumner, M. (2018)
Nowadays, the existing hierarchical, centrally controlled power grid faces new challenges due to the increase penetration of renewable sources, the need of implementing demand side management and the 2020 and 2050 environmental targets. A promising concept which can successfully contribute to addressing the environmental concerns and energy challenges of the 21st century is the grid-connected decentralised energy systems that embed significant amount of renewable generation and allow reverse power flow from distribution grids into the transmission network. Despite their benefits, decentralised energy storage systems are not yet widely spread due to several implementation and designing barriers. The design obstacle which is being addressed in this study includes the determination of the optimal size of the energy storage system components in terms of battery size and rating of the power converter for a single house application. In order to generalise the findings, 9 different real houses were considered. Thus, the most financially beneficial battery and power converter combination for 9 existing UK houses with installed PV roof-top system were identified in this study.